Analisis Komparatif Tindak Pidana Penipuan Dalam KUHP Kolonial dan KUHP Nasional - Delvi Paluaran; Sunardi Purwanda; Aksah Kasim; Jumardin Jumardin (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
The crime of fraud is a crime whose object is property. In the old colonial Criminal Code (a term for colonial products), this crime was regulated in Chapter XXV, ranging from Article 378 to Article 395, termed as